The Role of RSV Infection in Asthma Initiation and Progression: Findings in a Mouse Model - Junyan Han; Katsuyuki Takeda; Erwin W. Gelfand (Pulmonary Medicine)
Respiratory syncytial virus (RSV) is a common cause of severe lower respiratory tract diseases (bronchiolitis and pneumonia) during infancy and early childhood. There is increasing evidence which indicates that severe pulmonary disease caused by RSV infection in infancy is associated with recurrent wheezing and development of asthma later in childhood. However, the underlying mechanisms linking RSV infection to persistent airway hyperresponsiveness and dysfunction are not fully defined. To study these processes in ways which are not available in humans, animal models have been established and have provided valuable insight into the pathophysiology of RSV-induced disease. In this paper, we discuss experimental models of RSV infection in mice and highlight a new investigative approach in which mice are initially infected as neonates and then reinfected later in life. The findings shed light on the mechanisms underlying the association between early severe RSV infection and development of asthma later in childhood.